Dyeing of screw pine (Pandanus tectorius) leaves using natural dyes from local plants in Songkhla Province, Thailand - Teeparuksapun, Kosin; Prasongchan, Nicha; Wunsri, Supranee; Joyphod, Phattarapha; Podkumnerd, Noppadon (Asia-Pacific Journal of Science and Technology, 2024)
This study had investigated and discussed the dyeing of screw pine (Pandanus tectorius) leaves by using natural dyes from four local plants, namely, turmeric rhizomes, as well as teak, mango, and mangosteen leaves, found in Songkhla Province, Thailand. A sample of screw pine leaves were dyed using 2% aluminum potassium sulfate (KAl(SO4)2) for the dye mordanting process, which resulted in good color adhesion. Dyes obtained from turmeric rhizomes, as well as teak, mango, and mangosteen leaves produced yellow, reddish-purple, yellow-green, and orange colors, respectively. The color coordinate of the four dyes was investigated and reported. The tensile properties test showed that the dyed screw pine leaves exhibited good strength. Moreover, ozone treatment was found to decontaminate microbes and enhance the storage stability of the materials. The technology was then transferred to the Screw Pine Handicraft Community in Khlong U-Tapao River Basin, Songkhla Province, Thailand. This transfer of knowledge will enable the community to produce various different dyed screw pine leaf products that would generate a source of sustainable income.